J. B. Hall – A. L. Ritchie – M. J. Edwards (ed.) - Helen Lovatt (Exemplaria Classica, 2010)
J. B. Hall – A. L. Ritchie – M. J. Edwards (ed.), P. Papinius Statius. Thebaid and Achilleid. Volume I. Text and Critical Apparatus. Edited by J. B. Hall, in collaboration with A. L. Ritchie and M. J. Edwards, Newcastle: Cambridge Scholars Publishing, 2007, pp. xxxviii + 441, ISBN 9781847183538.  J. B. Hall – A. L. Ritchie – M. J. Edwards (ed.), P. Papinius Statius. Thebaid and Achilleid. Volume II. Translated by A. L. Ritchie and J. B. Hall in collaboration with M. J. Edwards, Newcastle: Cambridge Scholars Publishing, 2007, pp. viii + 292, ISBN 9781847183535.  J. B. Hall – A. L. Ritchie – M. J. Edwards (ed.), P. Papinius Statius. Thebaid and Achilleid.Volume III. Discussion and secondary apparatus by J. B. Hall, in collaboration with A. L. Ritchie and M. J. Edwards, Newcastle: Cambridge Scholars Publishing, 2008, pp. 774, ISBN 9781847184900.